The Effect of Visual Learning Style on Learning Outcomes in Arabic Subjects - Norhidayah Norhidayah (Al-Muyassar: Journal of Arabic Education, 2023)
Learning style is a way to absorb, organize, understand and respond to information or teaching materials. There are three kinds of learning styles proposed by Bobbi De Porter and Mike Hernacki, namely: Visual Learning Styles, Audio Learning Styles and Kinesthetic Learning Styles. This visual learning style relies on learning activities on the subject matter he sees. In this visual learning style which plays an important role in the way of learning is vision. The purpose of this study was to describe the effect of visual learning styles on learning outcomes in Arabic subjects in Man City, Palangka Raya. This study uses a quantitative approach and the method used is descriptive. Data collection techniques in this research are questionnaires, documentation and interviews. Data analysis in this study analysis SPSS. The results of this study indicate that there is an influence of visual learning style on learning outcomes with the acquisition of a significant score of 0.00 < 0.05 in Arabic subjects in Man City, Palangka Raya. Gaya belajar merupakan cara untuk menyerap, mengatur, memahami dan merespon informasi atau bahan ajar. Ada tiga macam gaya belajar yang dikemukakan oleh Bobbi De Porter dan Mike Hernacki yaitu: Gaya Belajar Visual, Gaya Belajar Audio dan Gaya Belajar Kinestetik. Gaya belajar visual ini mengandalkan aktivitas belajarnya kepada materi pelajaran yang dilihatnya. Pada gaya belajar visual ini yang memegang peranan penting dalam cara belajarnya adalah penglihatan. Tujuan penelitian ini adalah untuk mendeskripsikan pengaruh gaya belajar visual terhadap hasil belajar pada mata pelajaran bahasa arab di Man Kota Palangka Raya. Penelitian ini menggunakan pendekatan kuantitatif dan metode yang digunakan adalah deskriptif. Teknik pengumpulan data dalam penelitin adalah angket, dokumentasi dan wawancara. Analisis data pada penelitian ini menggunakan SPSS. Hasil penelitian ini menunjukkan bahwa terdapat pengaruh gaya belajar visual terhadap hasil belajar dengan perolehan nilai signifikan 0,00 < 0,05 pada mata pelajaran bahasa Arab di Man Kota Palangka Raya.